Yellow leaf spot of winter bread wheat in the Saratov region - E. A. Konkova; S. V. Lyashcheva (Зерновое хозяйство России, 2020)
The purpose of the current work was to study the development of tan spot, the causative agent of yellow leaf spot Pyrenophora tritici-repentis (Died) Drechsler on winter bread wheat in the conditions of the Saratov region of Russia. In 2018–2019 there was carried out an estimation of the resistance of 33 winter bread wheat samples to the causative agent of yellow leaf spot. It was established that the varieties “Gostianum 237” and “Levoberezhnaya 1” were characterized by a high level of resistance in the fields. There were identified such weak susceptible varieties as “Victoria 95”, “Gubernia”, “Mironovskaya 808”, “Donskaya bezostaya”, “Smuglyanka”, “Kalach 60”, “111-96 / Zhemchuzhina Povolzhiya”, “L 329 / Urozhaynaya”, “Gubernia / Zhemchuzhina Povolzhiya”, “Saratovskaya 90/ Ukraina”, “L 503 / M Freeman”, “81-93 / (Saratovskaya 11 / Kharkov 82)”. There was identified a moderate damage in the varieties “Lutenscens 230”, “Saratovskaya 80”, “Saratovskaya 90 / 14431 M”, “Sozvesdie”, “Anastasia”, “Saratovskaya 8 / Yubilyar”. The varieties “Zhemchuzhina Povolzhiya”, “Saratovskaya 17”, “Elvira”, “Saratovskaya 8 / B.Z.D.”, “(26-72 / N 49)/(L 15 / Pia)/Sar. 8)”, “Saratovskaya 8 / Yubilyar”, “L 503 / M Freeman”, “30-99/(Saratovskaya 11 / Kharkovskaya 82)”, “Sharada / L 31-98”, “346-06 / L 1334-5”, “Saratovskaya 90”, “L 329 / Saratovskaya ubileynaya”, “Istok/(Saratovskaya 90 / L 503)”, “Brigantina / Don 74” were found susceptible to the pathogen. It was identified that the proportion of winter soft wheat samples resistant to Pyrenophora tritici-repentis was 42% of the total number of varieties studied. There was studied dynamics of Pyrenophora tritici-repentis development in the winter soft wheat variety “Saratovskaya90”. It was found out that the damage degree of the winter bread wheat variety “Saratovskaya90” greatly depended upon the remoteness of the sowings from the source of infection.